Multidimensional profiling of rugby league players: A systematic scoping review and expert Delphi consensus - Sam Wild; Cameron Owen; Ben Jones; Sam McCormack; Omar Heyward; Sean Scantlebury; Dave Rotheram; Neil McCarthy; Kevin Till (PLoS ONE, 2025)
Player profiling can aid talent identification and development by highlighting strengths and weaknesses, and evaluating training interventions. However, there is currently no consensus in rugby league on the qualities, skills, and characteristics (i.e., factors) which should be profiled, or the methods to use to assess these factors. Consequently, the aims of this two-part study were to 1) establish the most common factors and methods for profiling rugby league players, through a systematic scoping review, and 2) develop consensus on the factors and methods experts believe should be used when profiling rugby league players. In Part 1, a systematic scoping review of studies profiling rugby league players was conducted according to the PRISMA guideline for Scoping Reviews. In Part 2, a panel of 32 experts were invited to participate in a sequential three-round Delphi consensus, used to identify the factors that they believed should be profiled in rugby league players and associated methods of assessment. Part 1 identified 370 studies, which assessed varying numbers of factors from five higher order themes; physical (n = 247, 67%), health-related (n = 129, 35%), other (n = 60, 16%; e.g., playing experience, level of education), technical-tactical (n = 58, 16%), and psychological (n = 25, 7%). Only 3% of these studies featured female participants (n = 11). In Part 2, 120 factors were initially identified, of which 85 reached consensus (≥70% agreement). This included 22 physical, 22 psychological, 20 technical-tactical, 15 health-related, and six player information factors. Collectively, these findings evidence the multidimensional nature of talent in rugby league, highlighting a range of factors across several domains that should be considered when identifying and monitoring talent in the sport. Furthermore, technical-tactical and psychological factors were identified as areas for future research, due to the large number of factors which reached consensus in these areas and the comparatively low amount of research conducted in them.